PENGARUH FOKUS PADA KONSUMEN DAN PERBAIKAN BERKELANJUTAN TERHADAP BUDAYA KUALITAS (STUDI PADA KARYAWAN CV. AUTO SEJAHTERA BANDA ACEH ) - Banta Karollah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2014)
Research title : The Effect of Focus on Consumer And Sustainable Mending to the Quality Culture (Case Study in CV. Auto Sejahtera Banda Aceh Workers).This research is empirical study which examine about the effect of consumer focuses and sustainable mending to the quality culture. It conducted in CV. Auto Sejahtera Banda Aceh auto repair shop. Data colected is examined by simple linier regression model which processing by Statistical Product and Service Solution software.The estimation result can be concluded as receive the alternative hypothesis and reject null hypothesis conversely. Which means that respondent completely expressed to the research indicators. Hence, research variables is significanltly and simultanously effect to the quality culture in Auto Sejahtera Banda Aceh auto repair shop. As follows, on the t test it also effect quality culture partially, by t statistic value 8, 199 and 2,458 respectively greater than t satistical table and the most effecttive variable is consumer focuses